Stigmasterol alleviates endplate chondrocyte degeneration through inducing mitophagy by enhancing PINK1 mRNA acetylation via the ESR1/NAT10 axis - Li Hao; Chen Xiaofeng; Huang Baoci; He Junjie; Xie Junxian; Guo Weijun; Liang Jinjun; Ruan Jiajian; Liu Jincheng; Xiang Zhen; Zhu Lixin (Open Life Sciences)
Intervertebral disc degeneration (IVDD) is a core factor in spinal degeneration. To date, there is no effective treatment for IVDD. It is urgent to identify the pathogenesis of IVDD to develop effective strategies for IVDD treatment. Alleviating endplate chondrocyte degeneration is a promising strategy for IVDD treatment, while mitophagy prevents degeneration of endplate chondrocytes. Stigmasterol (STM) protects neurons from injuries by triggering mitophagy, yet the effect of STM on the mitophagy of endplate chondrocytes in IVDD has not been reported. In this study, endplate chondrocyte degeneration was induced by interleukin-1β, and the ribonucleic acid (RNA) acetylation level was identified by acetylated RNA immunoprecipitation. Herein, results indicated that STM alleviated endplate chondrocyte degeneration. Besides, STM induced PTEN-induced kinase 1 (PINK1)-mediated mitophagy in degenerated endplate chondrocytes. Moreover, N‐acetyltransferase 10 (NAT10) increased PINK1 expression by improving PINK1 mRNA acetylation in endplate chondrocytes. In addition, STM regulated NAT10 expression by estrogen receptor 1 (ESR1) in degenerated endplate chondrocytes. In summary, the present study revealed that STM attenuated endplate chondrocyte degeneration through inducing mitophagy by enhancing PINK1 mRNA acetylation via the ESR1/NAT10 axis. These findings would provide novel strategies for the treatment of IVDD.